Production and Determination of Some Biochemical Properties of Protease Enzyme by Trichothecium roseum Under Solid State Fermentation - Ozkan, Ebru; Ertan, Figen (ARS DOCENDI, 2012)
Some fungal species were searched in terms of protease production by using casein degrading protease screening methods and it was found that Trichothecium roseum Penicillium piceum, Penicillium chrysogenum and Aspergillus wentii had the highest protease activity. Solid state fermentation was carried out by using wheat bran as substrate and it was determined that T. roseum had the highest protease activity. A number of culture conditions for protease production by T. roseum under SSF were investigated. Maximal protease production was obtained with initial moisture content of 85 % (w/v), an inoculum level of 2 mL (1x10(6) spore/mL) when incubated at 30 degrees C for 7 days. Maximum activity of protease with casein as a substrate was observed after 10 minutes at 40 degrees C temperature and at pH 6.5. The K-m and V-max values of protease for casein as substrate were calculated to be 6.06 (mg/mL) and 121.95 (U/mL), respectively.
Keywords: Protease; solid state fermentation (SSF); Trichothecium roseum; ALKALINE PROTEASE; THERMOPHILIC FUNGUS; PROCESS PARAMETERS; PENICILLIUM SP; OPTIMIZATION; METALLOPROTEASE; PURIFICATION; SUBSTRATE; Biotechnology & Applied Microbiology